2010
DOI: 10.4269/ajtmh.2010.10-0234
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic and Clinical Features of Cutaneous Leishmaniasis in Southeastern Tunisia

Abstract: Species-specific diagnosis was performed in 66 patients with cutaneous leishmaniasis (CL) living in Tataouine focus in southeastern Tunisia. Leishmania DNA was extracted directly from dermal scrapings (n = 66) and from parasites obtained in culture (n = 12). Species were identified by using polymerase chain reaction–restriction fragment length polymorphism analysis for internal transcribed spacer region 1 and isoenzyme analysis. Leishmania tropica and L. major were identified in 31 (47%) and 35 (53%) cases res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 12 publications
9
44
2
Order By: Relevance
“…killicki was first detected in the micro-focus of Tataouine in southeast Tunisia in 1980, in an epidemic of CL [4,48]. The first cases of L. major in Tataouine were only recorded in 1991 [49,50], but now chronic and zoonotic CL co-exist in this governorate [3][4][5]. In agreement with previous epidemiological reports, our analysis found that L. major and L. killicki (syn.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…killicki was first detected in the micro-focus of Tataouine in southeast Tunisia in 1980, in an epidemic of CL [4,48]. The first cases of L. major in Tataouine were only recorded in 1991 [49,50], but now chronic and zoonotic CL co-exist in this governorate [3][4][5]. In agreement with previous epidemiological reports, our analysis found that L. major and L. killicki (syn.…”
Section: Discussionsupporting
confidence: 81%
“…L.tropica) are the only species circulating in the Tataouine governorate. The isolates were collected in different villages of the investigated region, confirming the geographical spread of Leishmania [3,7,9]. Contrary to previous studies, the most abundant species was L. killicki, accounting for 80% of our sampling.…”
Section: Discussioncontrasting
confidence: 38%
See 3 more Smart Citations